Pengaruh Job Satisfaction dan Career Development terhadap Turnover Intention yang Dimediasi oleh Work Engagement pada Perusahaan Pertambangan - Robert Tua Barasa; Tissa Aulia Damayanti; Marissa Pusparini; C Christianingrum (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Significant turnover intention represents a strategic challenge in the mining industry, which relies heavily on competent human resources. This study investigates the influence of job satisfaction and career development on turnover intention, with work engagement serving as a mediating variable. Using a quantitative design, data were collected from 220 respondents and analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings confirm that job satisfaction and career development positively and significantly enhance work engagement. Furthermore, job satisfaction demonstrates a significant direct effect in reducing turnover intention. In contrast, career development does not show a significant direct influence on employees’ intention to leave the organization. Importantly, work engagement emerges as a crucial mediating mechanism linking job satisfaction and career development to lower turnover intention. These results imply that organizational interventions focused on satisfaction and career development are likely to be more effective when accompanied by efforts to strengthen employee engagement. The study contributes theoretically by enriching organizational behavior literature and offers practical implications for mining industry HR managers in designing more effective and sustainable employee retention strategies centered on enhancing work engagement.